DEVELOPMENT OF A MODEL FOR TRANSPORT AND LOGISTICS PROCESS USING HIERARCHICAL TIMED COLOURED PETRI NETS - Adigun, Oyeranmi; Okikiola, Folasade Mercy; Ayodeji, Idris (FUDMA JOURNAL OF SCIENCES, 2025)
Transport and logistics are important for modern supply chains, involving activities like warehousing, inventory management, distribution planning, and transportation. Ekeson Transport Company has a significant reliance on manual processing, resulting in prolonged queuing and waiting times, reduced service delivery, customer attrition, and revenue loss. To address this issue, a Hierarchical Timed Coloured Petri Net (HTCPN) model was developed using direct observation data from 20 observations at the company. The model consists of three sub modules: sender, reception, and receiver. The simulated values were validated using bivariate correlation coefficients, indicating the model can effectively manage sender and reception numbers, reduce queueing and waiting times. The result showed that the p-value obtained was less than the level of significance of 0.05, which depicts that the simulated values are a representation of the real system. Therefore, the model can be used in making decisions about the effective Transport and Logistics Services, thus reducing queueing time and waiting time.
Keywords: Transport; Logistic; Correlation; Simulation outputs